Anemia and its determinants among women of reproductive age in mid-western Terai of Nepal 2015. (2016)
SUMMARY: Despite a number of targeted interventions, anemia still poses a huge challenge by ruling one-third Nepalese women as anemic. According to Nepal Demographic and Health Survey 2006 and 2011, Anemia prevalence among women of reproductive age group is stagnant compared to the previous survey. Evidences assembled around the world provide an insight to many important contributors to anemia. Evidence around the factors contributing to anemia is scarce. Understanding what drives anemia among this vulnerable populace would be worthwhile, with a great significance on planning and implementing sensitive and specific nutrition interventions. Therefore, this study came as an endeavor with an objective of unveiling the determinants of anemia among women of reproductive age of Mid-western Taraiof Nepal. This was a descriptive, cross-sectional study executed in Dang, Banke, and Bardiya. A total of 849 (response rate: 99.7%, computed sample 852) women of reproductive age agreed to be the part of study, who were drawn through probability proportional to size sampling. The 781research participants (response rate: 91.7%) gave written consent for extraction of blood sample, and 791research participants (response rate: 92.8%) provided stool sample. A standard semi-structured questionnaire was employed to assess sociodemographic and behavioral aspects. Laboratory tests were done for blood and stool specimens using validated tool.The study soughtan approval from the Ethical Review Board of the Nepal Health Research Council. Trained enumerators underwent a faceto-face interview, after selected samples granted a written consent. Anthropometric measurements together with blood and stool sample collection were undertaken by a group of laboratory technicians in the following day. Stool samples were analyzed in the field laboratory set up made by the research team under close supervision of senior medical lab technologists. Blood specimens were transported the same evening to Kathmandu which was then handed over to Civil Service Hospital, Kathmandu for the analysis. Data were analyzed in Statistical Package for Social Sciences software full version 20. The results of the current study are presented on the ground of univariate and bivariate analysis. Socio-demographic features (n=849)  A large number of samples was shared by upper caste (39.1%), Hindu (92.5%), and married (88.3%).  Three out of ten received higher secondary and above education.  One-half were homemakers and the similar proportion lived in nuclear family.  The 69 out of 100 revealed an annual income of more than one lakh (of those responding). Reproductive health history (n=849)  Mean age at first menstruation counted 13.8± 1.4 years.  Mean duration of menstrual cycle was figured at 32.9± 14.7 days.  Mean days of bleeding during menstruation equaled to 4.6± 3.3 days.  Prevalence of self-reported normal menstrual cycle and normal bleeding days during menstruation was 83.5% and 93.3% respectively. Reproductive health history of married women (n=750)  Mean age at marriage was computed to be 17.3 ± 2.9 years.  Mean age at first child-birth was estimated to be 19.3±2.8 years.  Mean birth-interval was 41.9 ± 25.7 months, with birth interval of two years and more among 81.8%.  Of 718 (responding question), 21.0% experienced pregnancy wastage in the past, and 12.1% underwent a planned induced abortion. Health seeking behavior among those who became pregnant during last five years preceding the survey (n=358)  Nine out of ten (89.4%) paid an antenatal care visit; of which 72.5% made four or more visits.  Statistics of iron tablet and albendazole consumption during the last pregnancy was: 86.0% and 81.8% accordingly.  The 70.4% consumed vitamin A capsule after giving birth to last child.  Of 750 married women, 39.7% were using modern contraceptives in the last 12 months. Alcohol and tobacco use (n=849)  Among the total women13.5% ever consumed alcohol; from which 94.8% acknowledged consuming in the last 12 months.  Five out of 100 were smoking; of which 77.3% were daily smokers.  It was six out of 100 using smokeless tobacco products; of which 74.5% were daily users.  A 43.0% were exposed to second hand smoke. Illness pattern (n=849)  A10.4% was found to suffer from chronic illness during some point at their lives.  Twenty percent reported being ill in last one month. Dietary pattern in the last seven days (n=849)  Of 772 non-vegetarian, negligible percentage consumed meat (1.4%), fish (0.3%), egg (3.1%), and fruit (2.4%) daily in the last seven days.  About 81.0% did not consume fish in the last seven days; while it was 60.3%, 51.6%, and 47.8% for egg, milk, and fruit accordingly. Knowledge of anemia(n=849)  Term anemia was heard by 30.3%; of them 58.0% correctly defined, half reported knowledge on signs of anemia, and 60.7% were knowledgeable on specific diets to be taken to prevent anemia. Household food security and dietary diversity (n=849)  Considerable proportion (87.3%, 95% CI: 84.9-89.7) was found to have household food secure status.  Dietary diversity was visible among 67.8% participants(95% CI: 64.0-71.6). Prevalence of hookworm, roundworm, and giardiasis (n=791)  Hookworm, roundworm,and giardiasis were seen on 1.5%, 5.3%, and 14.7% participants. As for pregnant women, roundworm, and giardiasis was spotted in 4.3% and 8.7% samples. Prevalence of malaria (n=781)  None of the samples were malaria positive. Height, weight, and Body mass index (n=791)  Mean height was 152.4± 6.6 cm. Likewise, mean weight was 51.0± 8.9 kg. The proportion of underweight women constituted a total of 15.4%. Also, 18.8% were overweight. Status of anemia(n=735 for non pregnant, 46 for pregnant women)  Three out of ten (28.3%, 95% CI: 3.8-52.8) pregnant women were anemic. A sizeable proportion of anemic pregnant women came from disadvantaged janajati (42.9%) and farmers (36.4%).  For non-pregnant women, figure of anemia stood at 37.6% (95% CI: 31.9-43.3), and majority were mildly anemic (92.4%, 95% CI: 89.1-95.7). The highest prevalence in this stratum was found among <30 years (42.8%, 95% CI: 35.1-50.5), disadvantaged non-dalit Taraicaste (49.2%, 95% CI: 31.9-66.5), separated/divorced/widowed (46.7%, 95% CI: 4.7-77.7), students (40.0 %, 95% CI: 21.2-58.8), and those without dietary diversity (43.5%, 95% CI: 34.0-53.0).  For pregnant women, 4.3% anemic belonged to Banke, 15.2% to Bardiya, and 8.7% to Dang. While for non-pregnant women 9.9% anemic were from Banke, 15.8% from Bardiya, and 11.8% from Dang. Types of anemia  It was 2.4% who had sickle cell disorder. Not surprisingly, 94.7% sickle cell carrier was Tharu/Chaudhari. Interestingly, prevalence of sickle cell disorder was heavily localized in Bardiya district, with 84.2% sickle cell carriers.  Two out of 100 non-pregnant women (1.8%) were suffering from iron deficiency anemia. Correlates of anemia  None of the factors were related with anemia among pregnant women.  Significant socio-demographic drivers among non-pregnant women were: age group (p=0.008) and ethnicity (p=0.002).  Associated reproductive history factors among normal women included: number of children (p=0.009), currently breast feeding (p=0.002), and planned induced abortion (p=0.000).  Presence of chronic illness (p=0.003), dietary diversity (p=0.020), and milk products consumption in the last seven days (p=0.001) were also correlated with anemia among the normal women. With a depiction of substantial proportion of anemic women in both pregnant and nonpregnant groups, findings underscore necessity of nutrition interventions chiefly covering younger women <30 years, separated/divorced/widowed, farmers,disadvantaged janajati, disadvantaged non-dalit Tarai caste and students. Most importantly, considering the fact of 94.7% sickle cell carriers from Tharu community;awareness campaigns targeting Tharu community and training of health workers, female community health volunteers in sites heavily populated by Tharu is of utmost importance. As study uncovered the fact of lower awareness of anemia and substantial anemic from those without dietary diversity, health education campaigns with more stress on kitchen gardening should be on line at school and community settings.